Komunikasi Fatik pada Film Good Doctor dalam Kaitannya dengan Tachiba - Puspitasari, Lenny; Soepardjo, Djodjok; Roni, Roni (LP. Ma'arif Janggan Magetan, 2024)
Phatic Communication or Phatic Communion has started to be widely practiced recently with several theories and forms, especially in relation to Indonesian and English, but in Japanese, it is very limited. Researchers here want to conduct research on phatic communication in relation to the Japanese language. In Japanese, a similar concept to phatic communication has existed for a long time, it is even said that the Japanese language is hyperphatic or a society that is very strong in applying the concept of phatic communication in its daily life, although with a different name, shakou jirei (社交辞令). This research discusses phatic sentences in Japanese conversation found in the film Good Doctor which will be examined regarding their function and relationship in relation to tachiba or the relationship between the speaker and the interlocutor in a conversational situation which according to Haugh and Obana (2016) is divided into 2 relevant classification (1) chi’i 地位(social status) and (2) yakuwari 役割 (role, responsibility). The function of phatic sentences in Japanese was classified according to Jumanto (2014) with 12 functions in English conversation, while in this study the researchers examined phatic sentences that appeared in Japanese conversation in relation to the concept of tachiba in Japanese society. The research regarding phatic communication in Japanese is still very limited, even though it is very often found in the daily conversation, thus considered very interesting to research, especially in relation to the social values that very commonly known in Japanese society. This research is a qualitative descriptive study using the free-involved listening method and note-taking method to analyze the fatic expression in relation to the concept of tachiba in Japanese society.